Implementasi Akad Salam Dalam Pembiayaan Perbankan Syariah Di Indonesia - Putri, Berliana; Winario, Mohd (Multidisciplinary Journal of Religion and Social Sciences, 2024)
The purpose of this article is to discuss the implementation of salam contracts in sharia banking financing in Indonesia. This article uses a conceptual approach by analyzing literature related to the application of salam contracts in sharia banking. The research results show that the implementation of salam contracts in sharia banking in Indonesia has great potential to support sustainable and inclusive economic growth. Akad salam offers a fair and transparent financing solution, enabling farmers and commodity producers to obtain funds up front to finance the production process. This not only helps increase productivity but also stimulates economic aspirations in rural areas.